Analysis of the content of the third-grade middle school mathematics book according to algebraic thinking and the extent to which students possess it (Journal of the College of Basic Education, 2025)
The current research aims to (identify the availability of algebraic thinking skills in the mathematics book prescribed for the third intermediate grade (Part 1, Part 2), 4th edition, for the academic year (2023-2024 AD), and to identify the extent to which third intermediate grade students possess algebraic thinking skills) To verify the objective of the current research, the researchers adopted the descriptive analytical approach, and the basic research sample consisted of (1000) male and female students from the third intermediate grade, the second semester of the academic year (2024-2023 AD), and the sample was applied to the six directorates of Baghdad Governorate, namely (Rusafa I, Rusafa II, Rusafa III, Karkh I, Karkh II, Karkh III), and 4 schools were randomly selected from each directorate of Baghdad Governorate, i.e. (24) schools, and the research tools are (the tool for analyzing the content of the mathematics book prescribed for the third intermediate grade (Part 1, Part 2), 4th edition, for the academic year (2023-2024 AD) According to algebraic thinking skills, a tool for testing algebraic thinking, where (30) paragraphs were developed, the paragraphs were distributed over three skills as follows: the skill of using relationships and symbols (12) paragraphs, the skill of using multiple representations (15) paragraphs, the skill of using patterns and generalizations (3) paragraphs) Statistical methods were used in the (SPSS program ((T-test for one sample, and T-test for two independent samples, Pearson's correlation coefficient), where the results showed the following (third-grade middle school students possess algebraic thinking skills compared to the hypothetical average, with a statistically significant difference between the average performance of male and female students in favor of students on the same test, and through the results that were reached, some recommendations and proposals were presented that the researcher hopes to study and take into account.